2020
DOI: 10.4269/ajtmh.19-0304
|View full text |Cite
|
Sign up to set email alerts
|

Bacteremia Caused by Extended-Spectrum Beta-Lactamase–Producing Enterobacteriaceae in Vientiane, Lao PDR: A 5-Year Study

Abstract: Although there has been an increasing incidence of bacteremia caused by extended-spectrum betalactamase (ESBL)-producing Enterobacteriaceae (ESBL-E) across South East Asia, there are sparse data from the Lao PDR, where laboratory capacity for antimicrobial resistance surveillance is limited. We, therefore, retrospectively reviewed bacteremia caused by ESBL-producing Escherichia coli and Klebsiella pneumoniae between 2010 and 2014 at Mahosot Hospital, Vientiane, Lao PDR. Clinical and laboratory data relating to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 45 publications
1
9
0
1
Order By: Relevance
“… 9 Chang et al reported the trend of ESBL-producing E. coli bacteraemia in Laos from 2010 to 2014, increasing from 7.8% (4/51) to 34.7% (17/49). 10 A larger dataset from Microbiology/LOMWRU laboratory from 2004 to 2016, which included data from Chang et al , showed that the actual proportion increased five-fold from 7% (2/28) in 2004 to 35% (27/78) in 2016 ( figure 3 ). 8 Among 280/1,837 inpatients and outpatients at Mahosot Hospital with urinary tract infection (UTI) that yielded significant growth from 2010 to 2011, 194/280 (69%) grew E. coli .…”
Section: Resultsmentioning
confidence: 98%
“… 9 Chang et al reported the trend of ESBL-producing E. coli bacteraemia in Laos from 2010 to 2014, increasing from 7.8% (4/51) to 34.7% (17/49). 10 A larger dataset from Microbiology/LOMWRU laboratory from 2004 to 2016, which included data from Chang et al , showed that the actual proportion increased five-fold from 7% (2/28) in 2004 to 35% (27/78) in 2016 ( figure 3 ). 8 Among 280/1,837 inpatients and outpatients at Mahosot Hospital with urinary tract infection (UTI) that yielded significant growth from 2010 to 2011, 194/280 (69%) grew E. coli .…”
Section: Resultsmentioning
confidence: 98%
“…Angkor Hospital for Children used the ACORN LIS that is based on the Microsoft Access program [ 36 ]. Mahosot Hospital used a local LIS that is also based on the Microsoft Access program [ 37 ]. Sunpasitthiprasong Hospital used the MLAB program [ 38 ].…”
Section: Resultsmentioning
confidence: 99%
“…Angkor Hospital for Children used ACORN LIS which was based on Microsoft Access program [35]. Mahosot Hospital used a local LIS which was also based on Microsoft Access program [36]. Sunpasitthiprasong Hospital used MLAB programme [37].…”
Section: Resultsmentioning
confidence: 99%